Expresamos nuestras emociones y aprendemos a controlarlas - Rodríguez Goicochea, Teresa Marlene (2019)
The entitled session “We express our emotions and learn to control them” it was developed in the area of Social Personnel taking into account the competence: Builds their identity, as well as the ability: self-regulates their emotions and it has been gotten to achieve in the students the performance: Self-regulate their emotions in interaction with their partners, with teacher support, when applying basic self-regulation (breathing) strategies._x000D_ During the developed session were applied motivational and challenging activities that encouraged the achievement and active participation through dialogue with the purpose that students express what they feel and think._x000D_ It was taken into account the pedagogical processes such as motivation and exploration of previous knowledge, problematization, learning construction and information processing, evaluation and transfer in the didactic processes of the area._x000D_ The learning strategies were agreed with the interests and needs of first grade students in primary education.